Harmonisation of Space in an Industrial City: Social Guidelines - Artemova, Olga V.; Logacheva, Natalia M.; Savchenko, Anastasia N. (Economy of Regions, 2021)
Urban studies examine the development of industrial cities regarding the well-being of citizens, their needs and quality of life. Due to a new understanding of industrial cities as towns for people, the role and place of man in the urban space should be reconsidered. We developed a model for structuring the industrial city space based on a retrospective analysis of urban development. Further, we revealed the characteristics of shrinking cities and determined how the harmonisation of the urban environment influences the society. The interaction between physical and social spaces was analysedfrom the perspective of object-subject relations, enriching the understanding of the categories of place and entity (residential area, public space, etc.), as well as allowing citizens to deliberately transform their environment. Using content analysis, we confirmed that the harmonisation of the urban environment (physical space) stabilises social relations, since the population, government and business should reach a consensus to achieve the city’s goal and satisfy their own needs and interests. The results of the urban space analysis reveal the disparities between historical and modern buildings, natural and urbanised areas, industrial and residential city areas, etc., that should be eliminated. The directions of harmonisation of the urban space (revitalisation of industrial facilities and marginal areas, housing renovation) are proposed. We tested different approaches on the example of cities in the Chelyabinsk region by analysing their development stages, signs of decline, and urban characteristics. We are continuing to study the development of industrial cities. Public authorities and local governments can use the obtained results to elaborate urban development strategies, as well as implement the national projects «Housing and Urban Environment» and «Demography» at the regional and municipal levels.